Faktor Predisposisi dan Pendorong Perilaku Merokok Siswa Remaja SMA - Emanuel F.H. Deve; Petrus Romeo; Enjelita M. Ndoen (Journal of Health and Behavioral Science, 2019)
Smoking is a serious health problem among teenagers, marked by the increasing number of teen smokers every year. This study aimed to determine factors associating with smoking behavior in class XI students at SMAN 4 Kupang. This type of research was quantitative, with a cross-sectional study approach. The total sample was 71 people selected by a simple random sampling technique. Data analysis used the chi-square statistical test. The results showed that three variables, namely: knowledge, peer smoking habits, and self-image, associated with smoking behavior (p-value = 0.056; 0.051; 0.056; and 0.075, respectively). Therefore, the school should increase awareness and restrict the smoking behavior of students by enforcing rules and sanctions for students who smoke in the school environment.